Study the Influence of Atmospheric Drag and J2 Effect in a Close-proximity Operation at LEO - Sanjeeviraja, Thangavel; R, Santhanakrishnan; S, Lakshmi (International Journal of Engineering and Technology, 2018)
In this paper is to assess the mission stability and the influence of J2 effect and aerodynamic forces. To maintain the relative motion of satellites by using a feedback control law for tracking error bound in the presence of J2 perturbation. A constant relative orbit under the effect of earth oblateness and conservative forces is referred as J2 and targeting the presence of atmospheric drag. Although, Schweighart and Sedwick control strategy for satellite relative motion is considering both lift and drag forces. The simulation result shows a better performance with high accuracy than an elliptical orbit under J2 perturbation and atmospheric drag along in-track formation. The algorithm and control strategies is useful tools for analysing a future space mission.Â Â Â